Validation of the brazilian version of Guy's neurological disability scale Validação da versão brasileira da escala de incapacidade neurológica de Guy - Carolina R. Araujo; Luciano M. Simão; Mariana I. Ybarra; Natasha V.M.G. Faria; Caroline M. Botelho; Marcos A. Moreira; Antônio L. Teixeira; Marco A. Lana-Peixoto (Arquivos de Neuro-Psiquiatria)
The Guy's neurological disability scale (GNDS) has recently been introduced as a new measure of disability in multiple sclerosis. It is patient-oriented, multidimensional, and not biased towards any particular disability. The purpose of the present study was to validate the Brazilian version of the GNDS. The adaptation of the scale was based on the translation/back-translation methodology. Sixty-two patients with clinically definite multiple sclerosis (CDMS) according to Poser's criteria were recruited for this study. GNDS was administered individually to each subject. The EDSS and the ambulation index (AI) scores were assigned by a neurologist. The intraclass correlation coefficient and the Cronbach's alpha values of the Brazilian version of GNDS (0.94 and 0.83, respectively) were comparable to the original one (0.98 and 0.79, respectively). Furthermore, the factor analysis of the Brazilian version of GNDS suggested, as the original article, a four-factor solution which accounted for 68.8% of the total variance. The Brazilian version of GNDS was found to be clinically relevant as it correlated significantly with the EDSS and AI. In conclusion, the Brazilian version of GNDS can be considered an important tool to evaluate the disability in MS patients, with clinical usefulness and psychometrics soundness. A Guy's neurological disability scale (GNDS) é uma escala de incapacidade criada recentemente, orientada para o paciente, multidimensional, e que não privilegia nenhum tipo específico de incapacidade. O objetivo deste estudo é validar a GNDS para a língua portuguesa. A adaptação da escala foi feita através do método de tradução e re-tradução. Sessenta e dois pacientes com esclerose múltipla (EM) clinicamente definida de acordo com os critérios de Poser participaram deste estudo. A GNDS foi aplicada individualmente em cada paciente. O EDSS e o índice ambulatorial (IA) foram determinados por neurologista. A correlação intra-classe e o valor de Cronbach's alfa da versão brasileira da GNDS (0.94 e 0.83, respectivamente) foram comparáveis aos do artigo original (0.98 e 0.79, respectivamente). Como no artigo original, a análise fatorial da versão brasileira da GNDS sugeriu uma solução de quatro fatores que explicaria 68.8% da variação total. A versão brasileira da GNDS mostrou-se clinicamente relevante uma vez que se correlacionou com o EDSS e o IA. Em conclusão, a versão brasileira da GNDS pode ser considerada como um importante instrumento de avaliação incapacidade na EM com significado clínico e relevância psicométrica.